2022
DOI: 10.3390/nu14030611
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Health Effects of Rare Sugars in a CACO-2/HepG2 Coculture Model

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become the most prevalent liver disease worldwide and is impacted by an unhealthy diet with excessive calories, although the role of sugars in NAFLD etiology remains largely unexplored. Rare sugars are natural sugars with alternative monomers and glycosidic bonds, which have attracted attention as sugar replacers due to developments in enzyme engineering and hence an increased availability. We studied the impact of (rare) sugars on energy production, liver cell phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…The Caco-2/target-cell co-culture model is primarily used to explore the immune response of intestinal cells and its relation to the function of the intestinal barrier. Through the use of a Caco-2/HepG2 cell co-culture model, researchers found that alginate was less likely to induce intracellular fat accumulation compared to glucose, maltose, trehalose and inulin, suggesting that alginate may be more beneficial to individuals with NAFLD [99]. Camille et al identified that the Caco-2/TC7 cell line, derived from human cells, serves as an effective in vitro model for studying the molecular mechanisms of TICE enterocytes.…”
Section: Co-culture Models and Intestinal Organoidsmentioning
confidence: 99%
“…The Caco-2/target-cell co-culture model is primarily used to explore the immune response of intestinal cells and its relation to the function of the intestinal barrier. Through the use of a Caco-2/HepG2 cell co-culture model, researchers found that alginate was less likely to induce intracellular fat accumulation compared to glucose, maltose, trehalose and inulin, suggesting that alginate may be more beneficial to individuals with NAFLD [99]. Camille et al identified that the Caco-2/TC7 cell line, derived from human cells, serves as an effective in vitro model for studying the molecular mechanisms of TICE enterocytes.…”
Section: Co-culture Models and Intestinal Organoidsmentioning
confidence: 99%
“…Trehalose is a natural saccharide that could alter autophagy [ 88 ], initiating lysosomal temporary damage [ 89 ]. A health benefit for trehalose has been proposed in HepG2 cells [ 90 ]. The action mechanisms of trehalose may involve the inhibition of glucose transporters leading to AMPK-activation, which could affect the autophagy [ 91 ].…”
Section: Valuable Components From Natural Foods For the Treatment Of ...mentioning
confidence: 99%
“…Hence, in order to investigate the indirect interactions among multiple cells in different tissues or organs under physiological or pathological conditions, it was necessary to coculture multiple cells in vitro to replicate the natural in vivo environment . In the traditional two-dimensional (2D) coculture systems like transwell, cells exhibit significant differences in morphology compared with those growing in the natural three-dimensional (3D) environment in vivo. Additionally, the physiological or metabolic traits of cells cultivated on a 2D surface are entirely distinct from those present in vivo, thereby hindering the discovery of potential cellular interaction mechanisms. Hence, several methods have been developed in recent years to create compartmentalized carriers with intricate geometries capable of selectively encapsulating multiple cell types simultaneously for an in vitro 3D coculture.…”
Section: Introductionmentioning
confidence: 99%